JUDICIAL CONSIDERATION OF THE DEFENDANT’S OBJECTION IN DECISION NO. 46/PDT.SUS-PHI/2023/PN SBY - Ananda Chrisna D. Panjaitan; Frederica Celia Suwono; Ielien Dorothy Abigail; Ni Made Anggi Dwita Maharani (Universitas Katolik Indonesia Atma Jaya, 2026)
This study aims to analyze the judges’ considerations regarding the defendant’s exceptions in a civil case through a case study of Decision No. 46/Pdt.Sus-PHI/2023/PN Sby. Therefore, the author raises a legal issue concerning the impact of errors in stating the identities of the parties in a lawsuit, as well as the status of the land and building under SHM No. 352 as an object of conservatory attachment. This research employs a normative juridical method using a statutory and case approach. The findings indicate that the panel of judges granted several exceptions raised by the defendant, namely error in persona and obscuur libel. The court determined that the plaintiff’s claim contained formal defects. Consequently, the claim was declared inadmissible (niet ontvankelijk verklaard). This decision is consistent with the Supreme Court jurisprudence No. 601 K/Sip/1975 concerning the misidentification of a defendant and No. 81 K/Sip/1971 concerning the clarity of the object of a land dispute. The study demonstrates that, within the framework of civil procedural law, exceptions play an essential role as an initial mechanism for determining whether a claim is sufficiently proper to proceed to further judicial examination. Furthermore, the findings emphasize the importance of exercising greater precision when drafting a statement of claim, particularly with regard to the identities of the parties and the subject matter of the dispute, so that a claim is not dismissed merely due to formal defects.